Authority and the female body in the writings of Julian of Norwich and Margery Kempe - Herbert McAvoy, Liz (Studies in medieval mysticism, 2004)
An examination of ways in which the writings of Julian of Norwich and Margery Kempe were affected by traditional and contemporary attitudes towards women.